2019
DOI: 10.1186/s12894-019-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

Does preoperative percutaneous nephrostomy insertion worsen upper-tract urothelial cancer oncological outcome? A retrospective single center study

Abstract: Background Physicians doubt percutaneous nephrostomy (PCN) insertion on cancer related hydronephrosis patients causes tumor seeding and worse cancer control. In this article, we attempted to determine if preoperative PCN alters cancer control in upper tract urothelial cancer (UTUC) patients. Methods Retrospective analysis of UTUC patients in a single center from 2005 to 2015. Exclusion criteria included lymph node metastasis, and patients underwent perioperative adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…21 More directly relevant to the work described here, a retrospective analysis comparing 25 patients with UTUC who underwent nephrostomy placement with 639 who did not, demonstrated similar oncologic outcomes whether or not nephrostomy was placed. 22 Given that patients being treated with UGN-101 have LG UTUC, and with strategic nephrostomy placement (away from a calyx containing tumor), these authors postulate the risk of tract seeding is very low. In those without a tumor-free landing zone for nephrostomy placement, this risk must be balanced with the potential for increased oncologic control from UGN-101 administration as well as the risk of adverse events related to retrograde administration or a greater number of endoscopic ablations.…”
Section: Discussionmentioning
confidence: 99%
“…21 More directly relevant to the work described here, a retrospective analysis comparing 25 patients with UTUC who underwent nephrostomy placement with 639 who did not, demonstrated similar oncologic outcomes whether or not nephrostomy was placed. 22 Given that patients being treated with UGN-101 have LG UTUC, and with strategic nephrostomy placement (away from a calyx containing tumor), these authors postulate the risk of tract seeding is very low. In those without a tumor-free landing zone for nephrostomy placement, this risk must be balanced with the potential for increased oncologic control from UGN-101 administration as well as the risk of adverse events related to retrograde administration or a greater number of endoscopic ablations.…”
Section: Discussionmentioning
confidence: 99%
“… 27,28 In terms of complications, around 17% of cases require blood transfusion, with a 1% risk of emergency RNU or renal artery embolization 96 . In addition, tumor seeding of the nephrostomy tract is a potential risk in 0.75% of patients 12,97 . However, these findings are based on the conventional percutaneous approach using a 30 Fr sheath 94 and not a miniature nephroscope 98 .…”
Section: Surgical Setting Device and Techniquementioning
confidence: 99%
“…Though percutaneous procedures are inherently more invasive than retrograde endoscopic counterparts, percutaneous biopsies of UTUC have shown minimal risk of tract seeding and intravesical recurrence when compared against retrograde procedures (46,48,49). The process of percutaneous access can provide the additional benefit of facilitating nephrostomy tube placement, which may help treat severe hydronephrosis or impending renal failure for UTUC patients with little seeding risk (49). Conversely, studies of percutaneous resection of UTUC have shown an association of percutaneous resection with recurrence.…”
Section: Percutaneous Approachesmentioning
confidence: 99%
“…However, data from larger studies that are UTUC-specific is limited. In a 2019 comparison of 25 patients with UTUC and percutaneous nephrostomy placement compared to 639 UTUC patients without nephrostomy, Huang et al found that 20% and 30.8% of patients, respectively, had either local recurrence or distant metastasis, suggesting that percutaneous nephrostomies had little effect on risk of tumor seeding (49). At this time, there remains a scarcity of data with larger populations of UTUC patients who have undergone percutaneous nephrostomy tube placement, and the true effect of percutaneous nephrostomy on seeding risk has yet to be fully characterized.Retrograde endoscopic resection/ablation Endoscopic resection of UTUC may be performed as part of the initial ureteroscopic tumor visualization and biopsy, while both endoscopic resection and ablation can be curative treatments for low-grade disease.…”
Section: Percutaneous Approachesmentioning
confidence: 99%